2010
DOI: 10.1111/j.1600-0501.2010.01925.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dose reduction on multi‐detector computed tomographic images in evaluating the maxilla and mandible for pre‐surgical implant planning: a cadaveric study

Abstract: Significant dose reduction by lowering mA can be utilized for pre-surgical implant planning in multi-detector CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
1
4
1
Order By: Relevance
“…In our study, subjective visualization suggested that bone crest delineations have a minimal effect on image quality, with scores ranging from 1.75 to 2.30 (fair to good), consistent with the results of a previous study by Koizumi et al 20 The visualization of dentin or enamel was worst ( Table 2), indicating that they are inherently low-contrast structures (the difference between dentin and enamel regions was ,200 HU) 21 and susceptible to changes in exposure setting, especially for tube voltage settings. The visualization of mandibular structures was slightly better than that of maxillary structures, similar to the results presented by Pittayapat et al 22 This might be because most mandibular structures are well corticated.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, subjective visualization suggested that bone crest delineations have a minimal effect on image quality, with scores ranging from 1.75 to 2.30 (fair to good), consistent with the results of a previous study by Koizumi et al 20 The visualization of dentin or enamel was worst ( Table 2), indicating that they are inherently low-contrast structures (the difference between dentin and enamel regions was ,200 HU) 21 and susceptible to changes in exposure setting, especially for tube voltage settings. The visualization of mandibular structures was slightly better than that of maxillary structures, similar to the results presented by Pittayapat et al 22 This might be because most mandibular structures are well corticated.…”
Section: Discussionsupporting
confidence: 92%
“…The radiation dose measured in the optimized protocol was 301-334 mSv in our study, which is potentially comparable with or lower than the radiation dose used in CBCT devices. Compared with MDCT, measured radiation dose of our study is also apparently lower than the original dose used in regular scanning protocols but is still slightly higher than the results described by Koizumi et al 20 (stating that the radiation dose could be reduced to 298 mSv), who demonstrate that a radiation dose as low as 28 mAs could be used for pre-surgical implant planning. Our study covered regions such as the enamel, dentin and pulp cavity for potential periapical diagnosis, as mentioned in Table 2.…”
Section: Discussioncontrasting
confidence: 61%
“…Other advantages, such as the possibility of three-dimensional reconstruction of the evaluated structure and optimal contrast resolution, allow diVerentiation between tissues, so that the information obtained is utilized more eYciently compared with conventional radiographic techniques [26]. Computed tomography was for a long time considered a high-dose technique, but with the development of MDCT and low-dose protocols tailored for the diagnostic task, doses below 0.15 mSv are achievable [12]. Only a few studies have compared MDCT and clinical Wndings after extraction of lower third molars [11,22,27], therefore the aim of this study was to assess the reliability of MDCT in determining the surgical risk of the inferior alveolar neurovascular bundle in extractions of third molars.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have described that in more than 50% of reports in the literature, there was a significant reduction in effective dose without actually evaluating the effect of this reduction. Some authors have reported associations between dose reduction and increased image noise, which may degrade and reduce image quality [ 13 , 14 ].…”
Section: Discussionmentioning
confidence: 99%